Binary Bitwise Artificial Bee Colony as Feature Selection Optimization Approach within Taguchi's T-Method - Harudin N.; Ramlie F.; Wan Muhamad W.Z.A.; Muhtazaruddin M.N.; Jamaludin K.R.; Abu M.Y.; Marlan Z.M. (Hindawi Limited, 2023)
Forecasting; Large dataset; Optimization; Search engines; Artificial bee colonies; High dimensionality; Mahalanobis-taguchi systems; Objective functions; Optimization approach; Prediction accuracy; Prediction techniques; Suboptimal solution; Predictive analytics